The first Myrmecotypus O. P.-Cambridge (Araneae: Corinnidae) from Argentina: description of Myrmecotypus iguazu new species - Rubio, Gonzalo D.; Arbino, Manuel O. (Zootaxa, 2009)
The Castianeirinae genus Myrmecotypus was described by O. Pickard-Cambridge (1894) and currently includes eight species. All of them, except the atypical M. lineatus (Emerton 1909) (only record from USA), occur in the Neotropical region (known from Mexico to Panamá), Panamá being the southern most representative distribution of genus. Reiskind (1969) carried out the revision of the subfamily Castianeirinae Reiskind 1969 from North and Central America, concluding that much more study of more extensive collections will be needed to clarify the origin and distribution of South American species of this subfamily.